(untitled) (Research, Society and Development, 2022)
The objective of this work was to evaluate the use of different substrates and container volumes in the development of ’Xavante’ blackberry seedlings. The experimental design was a factorial scheme, with two levels for the substrate factor (Amafibra® coconut fiber and carbonized rice husk) and three levels for the container volume factor (10, 20 and 30 liters) and 12 levels for the (30, 60, 90, 120, 150, 180, 210, 240, 270, 300, 330 and 360 days). The microccutings were arranged in Nutriplan® black plastic pots with the volumes and with substrates tested. The percentage of survival, length of the largest stem (cm), number of stems per plant, number of shoots, length of the largest shoot (cm) and dry matter of the root were evaluated in the period of one year of the experiment. The chemical characteristics of substrates such as pH and electrical conductivity and physical properties such as water retention capacity and density at the beginning and at the end of the experiment were also evaluated. It was concluded that ’Xavante’ blackberry plants showed more adequate development in coconut fiber substrate, with 30 liter containers at 360 days of cultivation.